The Analysis of Character Building in Educational Values Found in Aladin Film Directed By Guy Ritchie - Sri arfani; Theresia Christina Putri (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
Learning media is a communication tool used to transmit knowledge, speed up the learning process, and raise educational standards. One can use movies as educational resources. Films tell a variety of tales that embody moral principles, including cultural, social, and educational principles. The 2019 film Aladdin is one option for a movie. The 2019 film Aladdin is an adaption of the 1992 original animated version. Guy Richie directed and John August and Guy Richie wrote the 2019 film Aladdin. Finding the character-building qualities in the 2019 Aladdin film and outlining how those educational values are portrayed in the film are the goals of this study. In this study, the author uses the educational value theory of Zaim El Mubarok in Hamidy (2017) which divides the value of educational consist of two namely; values of being and values of giving. Primary sources are film themselves and secondary sources are transcripts, books sources. The researchers have found in this film, several educations values can be drawn namely: 1) There are four educational values that can be learned in the section on the value of being, are: honest, brave, confidence, purify.2) There are five educational values that can be learned in the section on the value of giving, namely: loyalty, respect, not selfish, love and affection. Fair and Humanist